"Unborn Human Life and Fundamental Rights Leading Constitutional Cases Under Scrutiny": Pilar Zambrano y William L. Saunders (coords.) - Farfán Bertrán, María Laura (Derecho Público Iberoamericano, 2021)
Zambrano, Pilar and William L. Saunders (coords.), "Unborn Human Life and Fundamental Rights Leading Constitutional Cases Under Scrutiny", Berlin, Peter Lang GmbH, 2019, 264 pp.